Income Risk, Saving and Taxation: Will Precautionary Saving Survive? - Stefan Arent; Alexander Eck; Michael Kloss; Oskar Krohmer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
Former theoretical and empirical studies find that precautionary savings are reduced inthe presence of social security systems. The saving motive, however, does not change:individuals respond to increasing income risk by increasing their savings. Although thisstill holds for common tax and transfer systems, we show that this is not a feature of alltax and transfers systems. In contrast to former studies, we focus on the impact of thevariability of future income (higher degree risk).
Keywords: D11; D31; D91; H24; H31; 330; Income risk; saving behavior; social security; unemployment benefit; taxation; Vorsorgesparen; Einkommen; Risiko; Soziale Sicherung; Steuersystem; Sozialtransfer; Theorie